2009
DOI: 10.1007/s11695-009-0002-9
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte Accumulation of Long-Chain Fatty Acids in Obesity is Multifactorial, Resulting from Increased Fatty Acid Uptake and Decreased Activity of Genes Involved in Fat Utilization

Abstract: Background-The obesity epidemic causes significant morbidity and mortality. Knowledge of cellular function and gene expression in obese adipose tissue will yield insights into obesity pathogenesis and suggest therapeutic targets. The aim of this work is to study the processes determining fat accumulation in adipose tissue from obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 57 publications
1
46
0
2
Order By: Relevance
“…Its prevalence is increasing rapidly worldwide (3). Obesity stems from a positive mismatch between energy intake and energy expenditure, and is the pathological accumulation of triglycerides (TG) in adipose and other tissues (4,5). The World Health Organization (WHO) estimates that by 2015 approximately 2.3 billion adults will be overweight and more than 700 million will be obese (6).…”
mentioning
confidence: 99%
“…Its prevalence is increasing rapidly worldwide (3). Obesity stems from a positive mismatch between energy intake and energy expenditure, and is the pathological accumulation of triglycerides (TG) in adipose and other tissues (4,5). The World Health Organization (WHO) estimates that by 2015 approximately 2.3 billion adults will be overweight and more than 700 million will be obese (6).…”
mentioning
confidence: 99%
“…Intriguing recent results published by Walewski et al [9] showed that SPX may be a strongly anorexigenic factor involved in weight 4 regulation, with novel potential for obesity therapy. SPX may also be a fat-expressed satiety factor [10]. Recent findings also demonstrates a role for SPX in the control of cardiovascular/renal function and nociception [5,11].…”
Section: Spexin (Spx) Is One Such Intriguing Novel Neuropeptide a Prmentioning
confidence: 94%
“…A recent finding suggested that some SPX hypothalamic neurons take part in the central inhibition of food intake and energy homeostasis and the neuropeptide seems to be a potent anorexigenic factor in rats [9]. Furthermore, a previous microarray study reported that the SPX gene was distinctly depressed in adipose tissue of obese humans, and it is postulated that SPX is an adipokine, which would potentially impact food intake, energy expenditure as well as long chain fatty acid (LCFA) turnover [10]. Interestingly, a decreased serum SPX concentration was recently revealed in obese children compared with normal-weight controls without any correlation with adipokines and insulin levels [24].…”
mentioning
confidence: 99%
“…Adipose tissues play an essential role in energy homeostasis and constitute the largest energy reserve, in the form of triglycerides, in the body of animals (Walewski et al, 2010). A competition between biosynthesis and oxidation of fatty acids determines the distinct metabolic characteristics of adipose tissues.…”
Section: Introductionmentioning
confidence: 99%